2022
DOI: 10.1039/d2ta00583b
|View full text |Cite
|
Sign up to set email alerts
|

Different shapes based on ionic liquid leading to a two-stage discharge process

Abstract: During the discharging process, two-stage characteristics could be found near the negative electrode; it can be applied to optimize design concepts and boost the development of IL-based electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…The mechanism of these results was also studied using MD simulations. Near the negative electrode of [C n mim][AOT] and [C n mim][BF 4 ] systems, the structural transition of imidazolium-based NAILs and SAILs in a two-stage discharge process was discussed by Zhou et al [ 57 ]. The two-stage discharge process of NAILs was more obvious, and this process was slower for SAILs.…”
Section: Studies On the Mechanism Of The Charging And Discharging Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of these results was also studied using MD simulations. Near the negative electrode of [C n mim][AOT] and [C n mim][BF 4 ] systems, the structural transition of imidazolium-based NAILs and SAILs in a two-stage discharge process was discussed by Zhou et al [ 57 ]. The two-stage discharge process of NAILs was more obvious, and this process was slower for SAILs.…”
Section: Studies On the Mechanism Of The Charging And Discharging Pro...mentioning
confidence: 99%
“…Because of the two-stage discharge process of imidazolium-based ions [ 57 ], their discharging process is not equal to the reverse charging process. However, for other kinds of ions, such as surfactant-like ions [AOT] − or NAIL ions [BF 4 ] − , there is no two-stage discharging process, meaning their discharging process is nearly equal to the reverse charging process [ 57 ]. Therefore, the different ions should appear so.…”
Section: Studies On the Mechanism Of The Charging And Discharging Pro...mentioning
confidence: 99%
“…It could be seen that the intercalation of guest species into MXenes could expand the interlayer spacing and overcome sluggish kinetics. In addition to this, ionic liquids (ILs) have also been used to preintercalate MXene in recent years, which is an effective method to improve interlayer spacing. Yan et al reported that [Emim] + cations chemically confined in Ti 3 C 2 T x could provide more electroactive sites and more efficient channels for ion migration …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the development of self-assembled structures has attracted much attention for their potential applications in electrochemistry, separation, molecular catalysis, and drug delivery. Building blocks commonly have amphiphilic properties. By conducting the polymer and surfactant, aggregation structures such as globular clusters, bilayers, nanotubes, and vesicles were formed and investigated. , …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the development of self-assembled structures has attracted much attention for their potential applications in electrochemistry, 1 6 separation, 7 15 molecular catalysis, and drug delivery. 16 24 Building blocks commonly have amphiphilic properties.…”
Section: Introductionmentioning
confidence: 99%